2015
DOI: 10.5897/err2015.2431
|View full text |Cite
|
Sign up to set email alerts
|

Preschool childrens skills in solving mathematical word problems

Abstract: This study aims to investigate the mathematical word problem-solving skills of preschool children 5-6 ages. To achieve this objective, the data were collected in four preschools (n=162). A mathematical word problem test was used as data collection tools. In this study, it was found that the children's skills at solving mathematical word problems based on addition and subtraction were at a medium level. In terms of sub-categories, the children were found to do better with result-unknown problems but to have dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Arithmetic Story Problems. Owing to the age characteristics of the participants, the mathematical problems that young children are able to solve are limited [4]. Therefore, the difficulty level of the arithmetic story problems featured in this study complies with the early development trajectories of a normal child aged 4-6 years old [2].…”
Section: Intervention Designmentioning
confidence: 65%
See 3 more Smart Citations
“…Arithmetic Story Problems. Owing to the age characteristics of the participants, the mathematical problems that young children are able to solve are limited [4]. Therefore, the difficulty level of the arithmetic story problems featured in this study complies with the early development trajectories of a normal child aged 4-6 years old [2].…”
Section: Intervention Designmentioning
confidence: 65%
“…Within this framework of mathematical story problems, we attempted to examine the effects of AR intervention by comparing it with traditional 2D pictorial representation and then evaluating the performance of preschoolers before and after the exposure to the AR-based learning environment. Since Perihan [4] suggested that children can respond more easily to mathematical problems in word format rather than using symbols (e.g. plus and minus signs), only pictures and animations excluding symbols and text were presented to the participants.…”
Section: Intervention Designmentioning
confidence: 99%
See 2 more Smart Citations
“…It is related to the activity of finding solution of a problem, making connection between concepts in mathematics. As it has primary function in human's basic needs, the attempt to develop problem solving ability is started early (see [3] & [4]). In general, there are four steps in problem solving including orientation, preparation, application and reflection [5].…”
Section: Introductionmentioning
confidence: 99%